2020
DOI: 10.1371/journal.pone.0228018
|View full text |Cite
|
Sign up to set email alerts
|

Malaria-related hospitalization during childhood in Papua, Indonesia: A retrospective cohort study

Abstract: Background In endemic regions, the age distribution of malaria varies according to the infecting Plasmodium species. We aimed to delineate the pattern of malaria-related hospitalization from birth in Timika, Papua-an area co-endemic for P. falciparum and P. vivax Methods Between April 2004 and December 2013, infants born at Mitra Masyarakat Hospital, or presenting within the first 7 days of life, were enrolled retrospectively into a cohort study and followed passively using routinely-collected hospital surveil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…This study showed that the prevalence of plasmodium falciparum was higher than plasmodium vivax. This consistent with the national report of Indonesia government (5) and study in many parts of Indonesia (14,(16)(17)(18) and other countries including Ethiopia (19), Northwest Ethiopia (20) Saudi Arabia (21) , but this contrast with study in Mauritania (22) indicating the prevalence of malaria vivax was higher than falciparum. In this study, the prevalence of plasmodium falciparum shows a decreased trend from year to year, however the number of the cases was still high until the end of period under review.…”
Section: Discussionsupporting
confidence: 89%
“…This study showed that the prevalence of plasmodium falciparum was higher than plasmodium vivax. This consistent with the national report of Indonesia government (5) and study in many parts of Indonesia (14,(16)(17)(18) and other countries including Ethiopia (19), Northwest Ethiopia (20) Saudi Arabia (21) , but this contrast with study in Mauritania (22) indicating the prevalence of malaria vivax was higher than falciparum. In this study, the prevalence of plasmodium falciparum shows a decreased trend from year to year, however the number of the cases was still high until the end of period under review.…”
Section: Discussionsupporting
confidence: 89%
“…vivax is the second most prevalent human malaria parasite worldwide [2]. It is mostly absent from Central and West Africa, but causes significant morbidity in children elsewhere in the tropics [8][9][10]. More malaria-related hospital admissions in infants and toddlers are due to P. vivax than P. falciparum in the Asia-Pacific region, where both species are co-transmitted Antimalarial Resistance Network (WWARN) Data Platform, hosted by the University of Oxford, as part of the Impact of Malaria in Pregnancy on Infants Study Group.…”
Section: Introductionmentioning
confidence: 99%